Pseudocapacitance Induced Uniform Plating/Stripping of Li Metal Anode in Vertical Graphene Nanowalls. (21st October 2018) - Ren, Feihong; Lu, Ziyu; Zhang, Huan; Huai, Liyuan; Chen, Xinchun; Wu, Sudong; Peng, Zhe; Wang, Deyu; Ye, Jichun
Abstract: Unevenly distributed dendrite growth is usually viewed as a consequence to the diffusion‐limited interface instability during electrodeposition, leading to one of the most serious obstacles hindering the application of high‐capacity lithium (Li) metal anodes. Herein, a fundamental issue of modifying Li plating behavior using a structure of 3D vertical graphene nanowalls on nickel (Ni) foam (VGN/Ni) is investigated. Such a structure exhibits a significant pseudocapacitive interfacial feature, greatly improving the Li + ion transfer kinetic through the structure, and exhibiting uniform Li plating/stripping for stable Li metal cycling even at a high depth of discharge of 50%. Based on such a structure, high Coulombic efficiencies ≈97% and 99% can be obtained in carbonate and ether electrolyte over long‐term cycling. The symmetrical cell based on the VGN/Ni@Li composite anodes can afford a stable cycling of 2000 h with low voltage hysteresis of 30 mV. Full cell system using VGN/Ni@Li composite anode and LiFePO4 cathode is also proved, with high capacity retention of 89.4% at the 1000th cycle. The pseudocapacitance induced benefits, which have not yet been elucidated for Li metal anodes, can conduct to underlying strategy in designing stable Li metal host for high‐energy‐density batteries. Abstract : A pseudocapacitive surface of vertical graphene nanowalls is investigated to regulate Li plating/stripping behaviors. Very fast Li + ion transfer and uniform Li + adsorption/desorption are demonstrated as significant benefits by using such an advanced surface structure for stable Li metal cycling even at a high depth of discharge of 50%.